PENGARUH PERMAINAN SEBAGAI MEDIA PROMOSI TERHADAP PERILAKU GIZI SEIMBANG PADA SISWA SMA NEGERI 1 BAGAN SINEMBAH KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR RIAU TAHUN 2012 - Khoirani .; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Nutrition is a human basic need starting from the embryo in the womb until elderly. The problem of nutrition occurs because of a person’s behavior in nutrition is wrong, that is, the imbalance between the consumption of nutrition and the sufficiency in nutrition. The aim of the study was to know the influence of game as health promotion media on the balanced nutrition behavior among the student’s of Senior High School 1 of Bagan Sinembah, Bagan Sinembah subdistrict, Rokan Hilir District Riau in 2012. The type of the study was quasi experiment with one pre-test and post-test group design. The treatment was by games in the classroom. The measurement was done after four weeks.The samples comprised 52 student’s. A paired t-test was used to know the effectiveness of media. The result of the study showed that there of knowledge before and after treatment with t value = -5,131 and p = 0.000. The student’s attitude and practice about balanced nutrition also increase (t value = -7.392, p = 0.000 and t value = -12.460, p = 0.000) after treatment among four weeks. The result of reseach indicate that there was no increase in the nutritional status. The conclusion of the study showed that game media could increase teenager behavior on balanced nutrition although it did not influence nutritional status. It is recommended that the management of the school to use games as one of the alternatives in teaching such as history and biology for the senior high school student.   Keywords:  Behavior of  Balanced Nutrition, Nutritional Status, Game, Senior High School Student